Taxonomic notes on leptonetid spiders from the Ryukyu Archipelago with the description of two new species and the first record of the genus Longileptoneta from Japan (Araneae: Leptonetidae) - Ballarin, Francesco; Eguchi, Katsuyuki (Zootaxa, 2022)
The species belonging to the family Leptonetidae living in the Ryukyu Archipelago, Southwestern Japan, are herein discussed. Two species, Longileptoneta yamasakii sp. nov. and Masirana suzukii sp. nov., are described as new to science on the basis of both male and female. The new species were collected in caves in Yonaguni-jima Is. and Okinawa-honto Is., respectively the westernmost and largest islands of the Ryukyu arc. Longileptoneta yamasakii sp. nov. represents the first record of the genus Longileptoneta Seo, 2015 from Japan. The male and female of another leptonetid species previously known from the Ryukyus, Masirana longipalpis Komatsu, 1972, are redescribed and illustrated in detail. The internal genitalia of the female are shown and described for the first time.